Negative Emotions in Chinese Frontline Medical Staff During the Early Stage of the COVID-19 Epidemic: Status, Trend, and Influential Pathways Based on a National Investigation - Sun, Xiaoxiao; Xie, Fei; Chen, Beijing; Shi, Peixia; Shen, Sitong; Chen, Zhaohua; Yuan, Yuan; Zhang, Mengjia; Qin, Xuemei; Liu, Yingzhe; Wang, Yuan; Dai, Qin (Frontiers in Psychiatry, 2021)
Objective: The outbreak of coronavirus disease 2019 (COVID-19), declared as a major public health emergency, which has profound effects on public mental health especially emotional status. Due to professional requirement, medical staffs are at higher risk of infection, which might induce stronger negative emotions. This study aims to reveal emotional status of Chinese frontline medical staff under early epidemic to better maintain their mental health, and provide adequate psychological supports for them. Methods: A national online survey was carried out in China at the early stage of COVID-19 epidemic. Totally, 3025 Chinese frontline medical staff took part in this investigation with a general information questionnaire, Emotion Regulation Questionnaire (ERQ), and Berkeley Expressivity Questionnaire (BEQ). Results: At the early stage of COVID-19, anxiety was the most common negative emotion of Chinese medical staff, followed by sadness, fear, and anger, mainly at a mild degree, which declined gradually over time. Nurses had the highest level of negative emotions compared with doctors and other healthcare workers. Females experienced more fear than males, younger and unmarried medical staff had more anxiety and fear compared with elders and married ones. Risk perception and emotional expressivity increased negative emotions, cognitive reappraisal reduced negative emotions, while negative emotions led to more avoidant behavior tendency and more physical health disturbance, in which negative emotions mediated the effect of risk perception on avoidant behavior tendency in the model test. Conclusions: Chinese frontline medical staffs experience a mild level of negative emotions at early stage of COVID-19, which decrease gradually over time. The findings suggest that under epidemic, nurses' mental health should be extensively attended, as well as females, younger, and unmarried medical staff. To better ensure their mental health, reducing risk perception and improving cognitive reappraisal might be important, which are potentially valuable to form targeted psychological intervention and emotional guidance under crisis in the future.